IMPLEMENTASI STRATEGI PENGEMBANGAN PROGRAM KOTA SEHAT MELALUI KAWASAN MASYARAKAT SEHAT YANG MANDIRI DI KABUPATEN ROKAN HULU - Delisna Yanti; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Rokan Hulu district received the "Healthy District" award in 2019. This Healthy District assessment consists of 9 areas, one of which is an Independent Healthy Community Area. The Padapa Sehat area is very potential to be developed, because of the strategic location of Rokan Hulu. However, in reality, problems are still found in the development and implementation to create an Independent Healthy Community Area in Rokan Hulu. This study aims to determine the implementation of the Strategy for Developing Healthy Community Areas that are Independent in Rokan Hulu Regency, the supporting factors in the Implementation of the Strategy in developing the Healthy City/District Program through Independent Healthy Community Areas in Rokan Hulu Regency. The method used is descriptive qualitative method. Research information is determined by purposive sampling technique. Collecting data through observation, interviews and documentation as well as data analysis using descriptive qualitative methods. The results of this study indicate that the implementation of the Rokan Hulu Regency Program Development Strategy has been going well despite experiencing a few obstacles. Supporting factors for the Implementation of the Healthy City Program Development Strategy in Rokan Hulu are increasing public awareness of a healthy lifestyle, the role of community health cadres, cross-sectoral roles and budget support. Keywords: Bappeda Strategy, Health Office, Supporting Factors and Healthy District Program Development